PEMANTAPAN HUKUM DALAM SISTEM PERADILAN - Sri Wulandari Sri Wulandari (Serat Acitya, 2012)
Abstract In the development of the law of a country that wants to have an authoritative legal system should try to make its justice system to be "Last Fortress" for justice seekers that do not disappoint people seeking justice. Also need the support of a heightened awareness of the institutions in the justice system to function each. To reduce the "tangle" in the justice system and the need for a unified high sensitivity not only from the judges but also the justice system work, so as to restore public confidence. Required the addition of knowledge of the law for judges, Governmenment Lawyer, Legalpractitioners, making their performance more professional in dealing with various problems